2017
DOI: 10.1126/sciadv.1700006
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed gene control reveals rapid mRNA turnover

Abstract: Researchers develop a new method to show that messenger RNA molecules live much shorter lives in the cell than previously thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 61 publications
9
100
0
Order By: Relevance
“…As the correlation of PABA and mRNA stability is negative ( Figure S15) , Promoter Activity Buffering may be a property of stable transcripts, while Amplification may be a property of unstable transcripts. Cell-to-cell variability data for some genes are consistent with a change in mRNA stability ( Figure S15) , though steady-state protein levels are not sufficient to uniquely identify changes in mRNA stability (Baudrimont et al, 2017;Thattai, 2016;Zenklusen et al, 2008) . It is likely that many other biological processes, such as transcription elongation, transcription termination or protein-complex imbalance-mediated protein degradation can also play a role, and the precise biological factors that determine PABA will be unique to each gene.…”
Section: Titration Of Limiting Regulators Can Explain Paba In Synthetmentioning
confidence: 96%
“…As the correlation of PABA and mRNA stability is negative ( Figure S15) , Promoter Activity Buffering may be a property of stable transcripts, while Amplification may be a property of unstable transcripts. Cell-to-cell variability data for some genes are consistent with a change in mRNA stability ( Figure S15) , though steady-state protein levels are not sufficient to uniquely identify changes in mRNA stability (Baudrimont et al, 2017;Thattai, 2016;Zenklusen et al, 2008) . It is likely that many other biological processes, such as transcription elongation, transcription termination or protein-complex imbalance-mediated protein degradation can also play a role, and the precise biological factors that determine PABA will be unique to each gene.…”
Section: Titration Of Limiting Regulators Can Explain Paba In Synthetmentioning
confidence: 96%
“…Survey of mRNA stability in dinoflagellates using in vivo labeling method revealed quite diverse mRNA half-life in Karenia brevis ranging from 42 min to 144 h [75]. However, a recent report demonstrated that mRNA degradation may occur rapidly with some genes start to degrade as early as 2 min [76]. Utilizing RNA stabilization solution such as RNAlater and RNAlater ICE seems effective to stop the dinoflagellates gene expression without compromising RNA integrity [46].…”
Section: Challenges and Consideration In Dinoflagellates Transcriptommentioning
confidence: 99%
“…The program sums the CSC of ten codons and when 20 values equal o lower than -1.28 was found the program localized the position of the non-optimal codons 21 in the ORFs. 22 Young (Holstege et al, 1998), Brown (Wang et al, 2002), Hughes (Grigull et al, 2004), Coller (Presnyak et al, 2015), Struhl (Geisberg et al, 2014), Weis (Munchel et al, 2011), Gresham (Neymotin et al, 2014), Cramer (Sun et al, 2012) and Becskei (Baudrimont et al, 2017) CSCs of each of the datasets for the 61 yeast codons. Values range from -0.64 (negative correlation, green panels) to 1.00 (positive correlation, red panels).…”
Section: Localization Of Non-optimal Codons Stretches 16mentioning
confidence: 99%
“…Genome-2 wide mRNA half-life measurements showed poor correlation across different datasets and different 3 methods (and, in some cases, even between similar methods), classifying the same mRNA molecule as 4 stable and unstable. It makes the identification of stability sequence motifs and a global view of 5 transcription and translation dynamics in yeast a problematic task (Baudrimont et al, 2017;Harigaya and 6 Parker, 2016). Several features, such as mRNA secondary structure, sequence and structural elements 7 located within 5`and 3`UTR as well as the lengths of the transcripts can affect mRNA stability (Parker, 8 2012).…”
mentioning
confidence: 99%